1993
DOI: 10.1016/0014-5793(93)80269-z
|View full text |Cite
|
Sign up to set email alerts
|

Peroxynitrite modification of low‐density lipoprotein leads to recognition by the macrophage scavenger receptor

Abstract: Peroxynitrite is an oxidant which could be formed in the vasculature by the reaction of superoxide with nitric oxide. It is capable of modifying amino acid residues and of initiating lipid peroxidation. In the present study we have shown that peroxynitrite converts low density lipoprotein to a form recognized by the macrophage scavenger receptor and that this process is associated with modification of the protein and lipid, and with the oxidation of a-tocopherol to a-tocopherol quinone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
134
0
7

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 274 publications
(143 citation statements)
references
References 46 publications
2
134
0
7
Order By: Relevance
“…Many studies have demonstrated the ability of ONOO 2 to cause oxidative modifications of the LDL components (23)(24)(25)(26)(27). ONOO 2 -modified LDL (nitrated LDL) is recognized by the macrophage scavenger receptor (28), supporting the crucial role of ONOO 2 in atherogenesis (22). LDL is generally surrounded by extrinsic antioxidants, including albumin (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have demonstrated the ability of ONOO 2 to cause oxidative modifications of the LDL components (23)(24)(25)(26)(27). ONOO 2 -modified LDL (nitrated LDL) is recognized by the macrophage scavenger receptor (28), supporting the crucial role of ONOO 2 in atherogenesis (22). LDL is generally surrounded by extrinsic antioxidants, including albumin (29).…”
Section: Discussionmentioning
confidence: 99%
“…Other considerations make these questions crucial. Protein nitration by ONOO 2 could be either deleterious, because it has been reported to enhance allergic responses (28), or beneficial because it may function as a defense mechanism against the cytotoxic action of ONOO 2 (29). Denitration could appear beneficial in the first case, and beneficial or deleterious, depending on the products released by the denitration process, in the second case.…”
Section: Discussionmentioning
confidence: 99%
“…Peroxynitrite, therefore, as one of the main deleterious NO-derived ROS, produces further injurious effects on the cardiovascular system, namely on several distinct vascular and platelet mechanisms, including lipid peroxidation, augmentation of platelet aggregation or modification of LDL and promotion of its pro-atherogenic interaction with macrophages. 31,32 Fig 2. Serum MDA content (A), MDA/TAS index (B), and plasma nitrotyrosine levels (C) in the 5 rat groups under study at the end of the treatments.…”
Section: Discussionmentioning
confidence: 99%
“…NO is a relatively stable free radical that is unable to oxidize LDL directly under physiological conditions (22,23). However, it reacts rapidly with superoxide to form peroxynitrite (ONOO Ϫ ) (24), a reactive nitrogen species that promotes peroxidation of the lipid moiety of LDL in vitro (25). Proteins also appear vulnerable to ONOO Ϫ because the oxidant reacts in vitro with tyrosine residues to yield the stable product 3-nitrotyrosine (26).…”
mentioning
confidence: 99%